Borderline personality disorder features and sensitivity to injustice - Lis, Stefanie; Liebke, Lisa; Hauschild, Sophie; Thome, Janine; Schmahl, Christian; Kleindienst, Nikolaus; Bohus, Martin (Journal of personality disorders, 2018)
Hypersensitivity to injustice has been proposed to contribute to interpersonal dysfunction in borderline personality disorder (BPD). We investigated whether BPD features are related to sensitivity to injustice and whether justice sensitivity mediates the relationship between BPD features and aggressive behavior. In an online survey, subjects reported justice sensitivity from the perspective of a victim, an observer, a beneficiary, and a perpetrator as well as BPD features and their own aggressive behavior. Justice sensitivity was higher in participants with a clinically relevant degree of BPD features when they evaluated injustice from the perspective of a victim or an observer. Victim sensitivity partially mediated the relationship between BPD features and the frequency of aggressive behavior. The present study provides first data on the important role of sensitivity to injustice in those with marked BPD features. Particularly, victim sensitivity with its close link to angry reactions may contribute to interpersonal problems in BPD.
Published Online:March 2018
Gesehen am 11.10.2018